Amyloid structure determination in RELION‐3.1. Issue 2 (10th February 2020) - Scheres, Sjors H. W.
Abstract : Amyloid structure determination in RELION is increasingly popular, but may suffer from refinements becoming stuck in local minima. This paper describes a new method for initial model generation that may alleviate this problem. Abstract : Helical reconstruction in RELION is increasingly being used to determine the atomic structures of amyloid filaments from electron cryo‐microscopy (cryo‐EM) images. However, because the energy landscape of amyloid refinements is typically fraught with local optima, amyloid structure determination is often difficult. This paper aims to help RELION users in this process. It discusses aspects of helical reconstruction that are particularly relevant to amyloids, it illustrates the problem of local optima in refinement and how to detect them, and it introduces a new method to calculate 3D initial models from reference‐free 2D class averages. By providing starting models that are closer to the global optimum, this method makes amyloid structure determination easier. All methods described are open‐source and distributed within RELION ‐3.1. Their use is illustrated using a publicly available data set on tau filaments from the brain of an individual with Alzheimer's disease.